Geoscience research and outreach schools and public engagement - Tong, Vincent C. H.; Ohio Library and Information Network
From energy and water resources to natural disasters, and from changing climatic patterns to the evolution of the Earths deep interior, geoscience research affects peoples lives in many ways and on many levels. This book offers a stimulating cross-disciplinary perspective on the important relationship between geoscience research and outreach activities for schools and for the general public. The contributors academics, research scientists, science educators and outreach program educators describe and evaluate outreach programs from around the world. A section entitled Field-based Approaches includes a chapter describing an initiative to engage Alaskan communities and students in research, and another on problem-based learning in the field setting. The Online Approaches section discusses ways to connect students and scientists using online forums; use of the web and social media, including the United Nations University and its experience with the design of a web magazine featuring geoscience research; and video clips on marine geoscience created by students and scientists. The section on Workshop and Laboratory-based Approaches includes a chapter on teaching geochronology to high school students, and another describing an extracurricular school activity program on meteorology. The Program Design section presents chapters on Integrating Geoscience Research in Primary and Secondary Education, on ways to bridge research with science education at the high school level, and on use of online geoscience data from the Great Lakes. The concluding section, Promoting Research-enhanced Outreach, offers chapters on Geoscience Outreach Education with the local community by a leading research-intensive university, and on the use of research to promote action in Earth science professional development for schoolteachers. Geoscience Research and Outreach: Schools and Public Engagement will benefit geoscience researchers who wish to promote their work beyond academia. It offers guidance to those seeking research funding from agencies, which increasingly request detailed plans for outreach activities in research proposals. Policymakers, educators and scientists working in museums, learned societies and public organizations who wish to widen participation will also find this book useful. Together with the companion volume Geoscience Research and Education: Teaching at Universities, this book showcases the key role that geoscience research plays in a wide spectrum of educational settings.
Part I: Introduction : the context. Geoscience and educational research in outreach activities / Vincent C.H. Tong ; Perceptions of time matter: the importance of geoscience outreach / Samuel A. Bowring -- Part II: Field-based approaches. Engaging Alaska communities and students in cryospheric research / Kenji Yoshikawa, Elena B. Sparrow and Julia Stanilovskaya ; The Salish Sea Expedition: science outreach from the gangplank / K. Westnedge and A. Dallimore ; Problem-based learning in the field setting / Lung Sang Chan and Loretta M.W. Ho -- Part III. Online approaches. From local to extreme environments (FLEXE): connecting students and scientists in online forums / William S. Carlsen, Liz Goehring and Steven C. Kerlin ; Communicating scientific research through the web and social media: experience of the United Nations University with the Our World 2.0 web magazine / Brendan F.D. Barrett, Mark Notaras and Carol Smith ; Marine geosciences from a different perspective: "edutainment" video clips by pupils and scientists / J. Dengg, S. Soria-Dengg and S. Tiemann ; Small, subject-oriented educational resource gateways: what are their roles in geoscience education? / Matteo Cattadori, Cristiana Bianchi, Maddalena Macario and Luca Masiello -- Part IV. Workshop and laboratory-based approaches. The European experience of educational seismology / A. Zollo, A. Bobbio, J.L. Berenguer, F. Courboulex, P. Denton, G. Festa, A. Sauron, S. Solarino, F. Haslinger and D. Giardini ; EARTHTIME: Teaching geochronology to high school students in the US / Britta Bookhagen, Noah McLean, Robert Buchwaldt, Matthew Rioux, Francis Duds and Samuel Bowring ; Little meteorological workshop an extracurricular school activity for pupils / Kornelija ?Spoler ?Cani?c and Dubravka Rasol ; Grasping deep time with scaled space in personal environs / Bo Holm Jacobsen -- Part V. Programme design. Integrating geoscience research in primary and secondary education / Elena B. Sparrow, Leslie S. Gordon, Martha R. Kopplin, Rebecca Boger, Sheila Yule, Kim Morris, Krisanadej Jaroensutasinee, Mullica Jaroensutasinee and Kenji Yoshikawa ; Bridging scientific research and science education in high schools through authentic and simulated science experiences / Lucette Barber ; Using guided inquiry tools with online geosciences data from the Great Lakes / Sandra Rutherford -- Part VI. Promoting research-enhanced outreach. Communicating climate science from a data-centered perspective / Matt Rogers ; Geoscience outreach education with the local community / Jennifer Saltzman ; Using research to promote action in Earth science professional development for teachers / Chris King.
Includes bibliographical references and index.
Ava Avila
Keywords: Earth sciences -- Study and teaching; Electronic books